Religious Upbringing in Family - Szymańska, Maria; Marek, Zbigniew; Walulik, Anna (Central European Journal of Educational Research, 2020)
The article is aimed at eliciting the deep, profound meaning of the religious upbringing of the human who is endangered nowadays with the loss or reduction of his/ her own identity, the identity of community, particularly family. This upbringing infusing the integrity of the personal, and society can be seen in the human's integral development covering the centre of a person’s being, his/ her spirituality. Spirituality can be seen from different perspectives. Spirituality aligned with religious upbringing awakens reflection upon how necessary it is to consider it one of the most important factors for determining complex human development. Therefore, the aspect of the religious upbringing in family is undertaken by the authors of this article, who would like to exemplify the importance of it in the reference to the Diary written by Anna Potocka from the Działyńscy. The author belongs to that famous noble family in Poland, who successfully helped others in expressing their love to God.